Knowledge, Attitude and Practice among endodontists of Nepal in patient management during COVID-19 arena - Kunwar, Deepa; Subham, Snigdha; Nepal, Manisha; Khadka, Jwolan (Journal of Gandaki Medical College-Nepal, 2021)
Background: Coronavirus disease, 2019 (COVID-19) is an infectious disease caused by the severe acute respiratorysyndrome coronavirus 2 (SARS-CoV-2).COVID-19 is a global pandemic affecting all aspects of life in all countries. Endodontist are at inherent risk because of aerosol generating procedures. The objective of the study was to assess the knowledge, attitude and practice (KAP) among Endodontists of Nepal to combat the COVID 19 pandemic.Method:A web-based cross-sectional study was conducted among Endodontist of Nepal from March to June 2021.Convenient sampling method was adopted. The data were analysed using SPSS version 20.Descriptive statistics was performed, percentage and frequency distribution were assessed. Chi-square tests wereused to see the association between the categorical variables. A p-value of